2015
DOI: 10.3390/nu7031859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhaled Citronella Oil and Related Compounds on Rat Body Weight and Brown Adipose Tissue Sympathetic Nerve

Abstract: Citronella oil is one of the most famous Indonesian essential oils, having a distinctive aroma. As with other essential oils, it is crucial to explore the effects of inhalation of this oil. Therefore, the aim of this research was to elucidate the effects of inhalation of citronella oil and its components isolated from Cymbopogon nardus L. (Poaceae), Indonesian local name: “Sereh Wangi” on the body weight, blood lipid profile, and liver function of rats, as well as on the sympathetic nerve activity and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 8 publications
2
31
0
1
Order By: Relevance
“…We also found that the overall number of patients with Legionella -associated pneumonia at our hospital has increased in the past 5 years (Figure 2), which corroborates a CDC report describing a significant increase in disease occurrence in the past 15 years 6…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We also found that the overall number of patients with Legionella -associated pneumonia at our hospital has increased in the past 5 years (Figure 2), which corroborates a CDC report describing a significant increase in disease occurrence in the past 15 years 6…”
Section: Resultssupporting
confidence: 89%
“…In most cases, water cooling or air-conditioning systems directly contributed to transmission of the disease,6 whereas fountain water and portable water systems in hotels have also been implicated in a few cases 7,8. Incidence of Legionnaires’ disease in New York City increased by 230% from 2002 to 2009, and the outbreak in summer of 2015 involved 120 patients, resulted in 12 deaths, and carried a 10.6% fatality rate 6. The outbreak was centered in the South Bronx, the poorest urban country in United States, which is already struggling with a very high prevalence of asthma and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The terpenoids such as the (R)-(+)-CT, a major phytoconstituent of the essential oils of plants of the genus Cymbopogon and Eucalyptus presents excellent antifungal activity (AVOSEH et al, 2015, BATUBARA et al, 2015. In this study, it was observed that the (R)-(+)-CT showed excellent antifungal efficiency in 90% of the C. albicans strains.…”
Section: Discussionmentioning
confidence: 58%
“…The phytoconstituent (R)-(+)-CT, belonging to the group of the monoterpenoids, is one of the major substances of essential oils of aromatic plants, such as the ones of the genus Cymbopogon and Eucalyptus (AVOSEH et al, 2015, BATUBARA et al, 2015. The citronellal is isolated as a nonracemic mixture of the R and S enantiomers, and has shown to have several biological activities, among them, antimicrobial, antioxidant, herbicide, insecticide and repellent action (SCHERER et al, 2009, QUINTANS-JÚNIOR et al, 2011, BRITO et al, 2012, TOMAZ et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies investigated possible antibacterial (Echeverrigaray et al, 2008;Kotan et al, 2007;Mulyaningsih et al, 2011;Ngan et al, 2012;Nostro et al, 2013), antifungal (Kim and Park, 2012;Mahmoud, 1994;Pereira et al, 2015;Shin and Lim, 2004;Viollon and Chaumont, 1994;Zore et al, 2011), anti-lice (Gonzalez-Audino et al, 2011), repellent (Michaelakis et al, 2014;Semmler et al, 2014), lipolytic (Choi, 2006), anti-allergic (Kobayashi et al, 2016), anti-inflammatory (Abe et al, 2003;Su et al, 2010) and antispasmodic (Sadraei et al, 2013;Vasconcelos et al, 2016) properties. In vivo studies investigated possible cardiovascular (Bastos et al, 2009;Igor A C Menezes et al, 2010;Ribeiro-Filho et al, 2016), antidiabetic (Jagdale et al, 2016;Srinivasan and Muruganathan, 2016), anti-cholesterol (Batubara et al, 2015), antinociceptive (Brito et al, 2012;Renan G Brito et al, 2013), antihyperalgesic (Renan G , anti-anxiety (Umezu et al, 2002) and anticonvulsant (Sousa et al, 2006) activities. Most of the in vitro studies did not describe the isomeric form of CT used in the study.…”
Section: <Insert Table 3>mentioning
confidence: 99%